Acute exacerbation of idiopathic pulmonary fibrosis after SARS-CoV-2 vaccination. Issue 3 (10th March 2022) - Bando, Tomohiro; Takei, Reoto; Mutoh, Yoshikazu; Sasano, Hajime; Yamano, Yasuhiko; Yokoyama, Toshiki; Matsuda, Toshiaki; Kataoka, Kensuke; Kimura, Tomoki; Kondoh, Yasuhiro
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has spread worldwide and coronavirus disease 2019 remains a major health concern. Several SARS-CoV-2 vaccines have been produced and are playing important roles in the prevention of infection and worsening to a severe state, and in improving mortality [1]. However, some concerns about adverse effects related to SARS-CoV-2 vaccination have been raised. Recently, various adverse effects have been reported, but there is little data on adverse effects on the lungs [2]. Although the association between acute exacerbation of interstitial lung disease and vaccination is not yet clarified, this is the first case report describing the possibility that SARS-CoV-2 vaccination may trigger acute exacerbation https://bit.ly/3tpu6Cz